Mid Term Appraisal of Second Five Year Plan Sikkim - Planning Commission (Planning Commission, 1964)
The Ministry of External Affairs requested the Planning Commission to make an assessment of the progress of Second Five Year Plan of Sikkim. Accordingly the Planning Commission in consultation with the concerned central Ministries appointed a Team of technical experts which visited Sikkim from April 27 to May 3, 1964.
Report of the Technical Team